Herding Behavior and Its Impact on Market Volatility: Empirical Evidence from the Pakistan Stock Market - Farooq Shah,; Muhammad Imran,; Shiraz Khan, (Dialogue Social Science Review (DSSR), 2024)
This paper aims at establishing the relation between herding and volatility with a reference to the Pakistan Stock Market and emerging and empirical evidence on the gains made from collective behavior by investors. The investigation of investor sentiment during the period of stress is done with the help of CSAD, GARCH model researches, and Panel Regression. In this research, the study presents the findings that indicate that herding behavior contributes prominently to increased market vulnerability and fluctuation, particularly amidst increase in uncertainty due to stock fluctuations; this out rightly highlights that retail investors due to their tendency to herd, result in irrational price movements. Overall, given the fact that herding behavior within the context of the shadow banking system has major implications for pecuniary policies, the empirical evidence can potentially foster policymaking, provide suggestions to financial organizations, and draw further attention to risk management to decrease the realization of herding behavior’s detrimental impacts. The paper adds to the existing literature on behavioral finance, especially in emerging markets and enhances understanding of investor psychology’s implications for market stability. In conclusion this paper presents the limitations of the study and makes recommendations for further research which includes studying the impact that institutional investors as well as macroeconomic factors may have on herding and the volatility of the market.